Single nucleotide polymorphisms within MUC4 are associated with colorectal cancer survival - Lu, Shun; Catalano, Calogerina; Huhn, Stefanie; Hemminki, Kari; Försti, Asta (PLOS ONE, 2019)
Mucins and their glycosylation have been suggested to play an important role in colorectal carcinogenesis. We examined potentially functional genetic variants in the mucin genes or genes involved in their glycosylation with respect to colorectal cancer (CRC) risk and clinical outcome. We genotyped 23 single nucleotide polymorphisms (SNPs) covering 123 SNPs through pairwise linkage disequilibrium (r2>0.80) in the MUC1, MUC2, MUC4, MUC5AC, MUC6, and B3GNT6 genes in a hospital-based case-control study of 1532 CRC cases and 1108 healthy controls from the Czech Republic. We also analyzed these SNPs in relation to overall survival and event-free survival in a subgroup of 672 patients. Among patients without distant metastasis at the time of diagnosis, two MUC4 SNPs, rs3107764 and rs842225, showed association with overall survival (HR 1.40, 95%CI 1.08-1.82, additive model, log-rank p = 0.004 and HR 0.64, 95%CI 0.42-0.99, recessive model, log-rank p = 0.01, respectively) and event-free survival (HR 1.31, 95%CI 1.03-1.68, log-rank p = 0.004 and HR 0.64, 95%CI 0.42-0.96, log-rank p = 0.006, respectively) after adjustment for age, sex and TNM stage. Our data suggest that genetic variation especially in the transmembrane mucin gene MUC4 may play a role in the survival of CRC and further studies are warranted.